Recent Advances in Chemical Engineering Select Proceedings of ICACE 2015 - Regupathi, I.; Shetty K, Vidya; Thanabalan, Murugesan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The book introduces the outcomes of latest research in the field of Chemical Engineering. The book also illustrates the application of Chemical Engineering principles to provide innovative and state of the art solutions to problems associated with chemical industries. It covers a wide spectrum of topics in the area of Chemical Engineering such as Transfer operations, novel separation processes, adsorption, photooxidation, process control, modelling, and simulation. The book provides timely contribution towards implementation of recent approaches and methods in Chemical Engineering Research. It presents chapters focussed on several Chemical Engineering principles and methodologies of wide multidisciplinary applicability. The intended audience of this book will mainly consist of researchers, research students, and practitioners in Chemical Engineering and allied fields. The book can also serve researchers and students involved in multidisciplinary research.
Numerical study of heat transfer characteristics of nano-fluids in channel containing different shapes of submerged tube -- A Numerical Investigation Based On Heat Transfer and Fluid Flow Characteristics of Air in a Circular Tube Heat Exchanger with Inclined Ribs -- Experimental Studies Involving Flow Visualization over Non-circular Geometries -- Thermohydraulic transport characteristics of Micro Mixer in Micro Channel -- Esterification of ethanol and maleic acid in packed bed reactor catalyzed by sulfonic acid functionalized silica (SAFS) -- Batch drying of wheat in a multiple porous draft tube spouted bed -- Studies on drying characteristics of rhizomes of ginger (zingiberofficinalerosc) -- Cationic Dyes Sequestration from Aqueous Phase Using Biosurfactant Based Reverse Micelles -- Screening of solvents for deacidification of sardine oil -- Removal of CO2 in a Multistage Fluidized Bed Reactor by Activated Carbon Prepared from Green Coconut Shell -- Calculation of Hydroxyl Radical Concentration-An Indirect Method -- Mathematical Modelling on Particulate Removal in Multistage Dual-flow Sieve Plate Column Wet Scrubber -- Methanol and water crossover in a passive direct methanol fuel cell: mathematical model -- CFD studies on pressure drop for low reynolds fluid flows across orifice in similarly shaped micro channel.
Keywords: Chemistry, Technical; Biotechnology; Electrochemistry; Industrial Chemistry; Chemical Bioengineering; Electrochemistry